2008
DOI: 10.1364/oe.16.010841
|View full text |Cite
|
Sign up to set email alerts
|

Efficient excitations of radially and azimuthally polarized Nd^3+:YAG ceramic microchip laser by use of subwavelength multilayer concentric gratings composed of Nb_2O_5/SiO_2

Abstract: Cylindrical vector beams were produced from laser diode endpumped Nd:YAG ceramic microchip laser by use of two types of subwavelength multilayer gratings as the axisymmetric-polarization output couplers respectively. The grating mirrors are composed of high-and lowrefractive-index (Nb 2 O 5 /SiO 2 ) layers alternately while each layer is shaped into triangle and concentric corrugations. For radially polarized laser output, the beam power reached 610mW with a polarization extinction ratio (PER) of 61:1 and a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Several new methods of formation of LG scalar and vector modes of different orders in diode-pumped lasers on the base of Nd 3þ -and Yb 3þ -doped ceramics and crystals were developed at the Institute for Laser Science (ILS) of the University of Electro-communications, Tokyo, Japan in the period of 2004-2011. [80][81][82][83][84][85][86][87][88][89][90] The present article provides an overview of experiments on LG modes selection carried out at ILS. The data on LG modes selection in cw and pulsed Nd:YAG and Yb:YAG lasers on the base of crystals and ceramics active elements end-pumped by diodes or an external laser source are presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several new methods of formation of LG scalar and vector modes of different orders in diode-pumped lasers on the base of Nd 3þ -and Yb 3þ -doped ceramics and crystals were developed at the Institute for Laser Science (ILS) of the University of Electro-communications, Tokyo, Japan in the period of 2004-2011. [80][81][82][83][84][85][86][87][88][89][90] The present article provides an overview of experiments on LG modes selection carried out at ILS. The data on LG modes selection in cw and pulsed Nd:YAG and Yb:YAG lasers on the base of crystals and ceramics active elements end-pumped by diodes or an external laser source are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The article considers methods of generation of LG scalar and vector modes from low to very high orders using original mode selection techniques, which include shaping of the pump intensity profile, using intra-cavity elements: lenses with spherical aberration, axicons, uniaxial crystals, and using polarization selective mirrors. [80][81][82][83][84][85][86][87][88][89][90] Illustrations of the first reported record-high-order hollow LG pm modes as well as of multiring Bessel-like LG modes with the highly directional propagation of beams' central maximum or minimum are presented. The mechanisms of modes selection in schemes with intra-cavity lenses, uniaxial birefringent crystals and diffractive pumping are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The concentric and multilayer structure induced the artificial birefringence and resonant interference, and by proper design to the grating parameters like the layer thickness and numbers, groove pitch, and others, the grating could show desired transmittance or reflectance to both the transverse electric (TE, polarization parallel to grating groove) and transverse magnetic (TM, polarization orthogonal to grating groove) waves. In our experiment, the photonic crystal grating used as output coupler had a reflectivity of about 90% for TM wave and was transparent to TE wave at 1064 nm [27][28][29][30][31].…”
Section: Methodsmentioning
confidence: 95%
“…The polarization purity could be determined by the availability of an intracavity component having high axisymmetric-polarization selectivity. Aiming at these objectives, Li et al recently suggested and constructed an end-pumped Nd:YAG microchip laser to emit continuouswave CVBs by using an axisymmetric-polarization subwavelength grating as the output coupler, 10 where the simple and compact cavity confi guration and specially designed grating mirror provided the highest laser effi ciency ever reported as well as control over modal symmetry and polarization purity.…”
Section: Introductionmentioning
confidence: 99%